Psychosocial and cultural analysis of childlessness and its implications on women emancipation in South Western Nigeria: the counselling perspective (2014)
Studies show that the stereotype that childlessness is solely considered a woman's problem makes infertility a major disaster for childless women in Nigeria. This study adopted a cross sectional survey design to explore the extent to which Psychosocial and cultural factors correlate with perception of childlessness among women in South Western Nigeria. Multi-stage sampling technique was utilized to draw out five hundred and fifty-four males and seven hundred females with age range of 20-45 (X =30.4; SD=8.6) from South Western Nigeria. A synchronized instrument with three sub- sections titled Psycho socio-cultural assessment of childlessness (r=0.75) was utilized for data collection. Two Research questions were answered and six null hypotheses tested at 0.05 level of significance. Descriptive Statistics, Multiple Regression Analysis, Pearson Product Moment Correlation and t-test for independent samples were used for data analysis. Results show that Nigerians irrespective of tribe, gender, age, educational status, self-esteem and religion consider childlessness a taboo and hold women solely responsible. This outcome has implications for improved sexual and reproductive health policy with respect to gender mainstreaming and counselling interventions for childless women.